Macrolide-resistant Streptococcus pyogenes: prevalence and treatment strategies. Issue 5 (May 2015) - Silva-Costa, Catarina; Friães, Ana; Ramirez, Mario; Melo-Cristino, Jose
<x xml:space="preserve">Abstract</x> Although penicillin remains the first-choice treatment for Streptococcus pyogenes infection, macrolides are important alternatives for allergic patients and lincosamides are recommended together with β-lactams in invasive infections. S. pyogenes may exhibit macrolide resistance because of active efflux (mef genes) or target modification (erm genes), the latter conferring cross resistance to lincosamides and streptogramin B. Worldwide, resistance is restricted to a limited number of genetic lineages, despite resistance genes being encoded on mobile genetic elements. For reasons that are not completely clear, resistance and the associated phenotypes are highly variable across countries. Although resistance remains high in several countries, particularly in Asia, an overall decreasing trend of resistance has been noted in recent years, mostly in Europe. This decrease is not always accompanied by declines in macrolide consumption, suggesting significant roles of other factors in determining the dynamics of macrolide-resistant clones. Continued surveillance is needed to obtain further insights into the forces governing macrolide resistance in S. pyogenes.